MANUSIA BERDOSA: Kajian Hermeneutik Pengkhotbah 7:1-22 dan Implikasinya bagi Pemuda GMIM Musafir Kleak - Robot, Kevin Yeremia (Educatio Christi, 2023)
This article aims to present a writing about the results of the interpretation of Ecclesiastes 7:1-22 and connect with the youth of GMIM Musafir Kleak. This text gives an overview of human life that is not free from sin, if it is associated with the life of youth, then the problem of youth life is inseparable from negative behavior, which in a theological understanding is called sin. Things related to sin such as involving smoking, alcohol, free sex, nightlife and others. The approach used is a qualitative approach and uses the hermeneutic method of historical criticism to get the original and historical meaning of the text. This text explains all sinful human beings and the advice to live justly and wisely. The implication through this text is that young people should not judge each other and form groups that are exclusive to each other in the youth community but as part of church service, it is necessary to build a togetherness that strengthens each other.